UPAYA MENINGKATKAN KECERDASAN INTERPERSONAL MELALUI PENERAPAN MODEL MAKE A MATCH DENGAN KARTU PASANGAN PADA ANAK USIA 4-5 TAHUN DI PAUD MITRA HANDAYANI KECAMATAN TENAYAN RAYA PEKANBARU - Muharnis Muharnis; Zulkifli Zulkifli; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims To determine the application of the model make a match with partner cards can increase the intelligence of children in PAUD Mitra Handayani Kecamatan Tenayan Raya Pekanbaru. This research is a classroom action research is research done in class with the purpose of improving or enhancing the quality of practice learning research subjects are children PAUD Mitra Handayani Kecamatan Tenayan Raya Pekanbaru of numbering as many children as 15 children, consisted of 7 men and 8 women. Collecting data using observation and documentation. Based on the survey results revealed that 1) Interpersonal intelligence of children aged 5-6 years in PAUD Mitra Handayani Kecamatan Tenayan Raya Pekanbaru model application activities make a match with one less card berkriteria partner. after the model application activities make a match with the card pairs in the cycle I and II berkriteria well. 2) The application of the model make a match with a partner card providing the possibilities of a rich learning and fun for children, so that children spontaneously would be interested in this game. 3) The application of the model make a match with partner cards can increase interpersonal intelligence of children aged 4-5 years in early childhood Handy Mitra Raya subdistrict Tenayan Pekanbaru.4) In testing the hypothesis can be seen an increase gained from each cycle. Where an increase in interpersonal intelligence obtained prior to action for the first cycle increased by 30.2%. While the improvement of interpersonal intelligence from the first cycle to the second cycle of 48.6%, and the overall improvement of interpersonal intelligence from initial data to the second cycle of 93.4%.Keywords: Interpersonal Intelligence, Model Couple Make A Match Card